The Swinging Pendulum of the Game Nations Play in International Relations: A Duplicity Diplomacy - Madubuko, Christian C. (American Journal of International Relations, 2024)
Purpose: This paper endeavours to critically interrogate the concept of "duplicity diplomacy," positing it as an essential framework for understanding the oscillating strategies employed by states amidst the complexities of contemporary international relations. The aim is to unveil the inherent contradictions and strategic necessities that underlie this phenomenon, particularly in the context of an increasingly multipolar global landscape. Materials and Methods: The research employs a qualitative methodology that integrates a multi-faceted analysis of empirical case studies involving significant geopolitical players. This approach encompasses semi-structured interviews with seasoned diplomats to capture experiential insights, a comprehensive content analysis of diplomatic communications to identify patterns and nuances in language and intent, as well as systematic reviews of contemporaneous media portrayals to contextualize public perceptions. By triangulating these methods, the study aims to enrich the understanding of duplicity in statecraft. Findings: The findings indicate that duplicity diplomacy transcends a mere catalogue of deceit, emerging as a strategic necessity reflective of the intricate complexities and contradictions that characterize our current multipolar world. Empirical illustrations reveal how states frequently oscillate between cooperative rhetoric and competitive actions, engaging in ostensible displays of loyalty while simultaneously pursuing self-interested goals through subterfuge. Notably, instances of strategic alliances undermined by covert operations serve to illustrate the double-edged nature of duplicity, where short-term gains often precipitate long-term repercussions that undermine international trust and stability. Implications to Theory, Practice and Policy: The analysis raises substantial questions regarding the ethical frameworks governing diplomatic practice in the context of growing global interdependence. It posits that as the stakes of international interactions escalate, the propensity for duplicity in state behaviour is likely to intensify, necessitating a critical re-evaluation of both scholarly and practical approaches to diplomacy. This discourse invites policymakers and scholars alike to consider how established norms around transparency and accountability can be reconciled with the inherent contradictions of statecraft.